The Garotters - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Garotters" by William Dean Howells is a comedic novel written in the late 19th century. It explores the themes of mistaken identity and social morality in the context of a robbery and the ensuing chaos that follows. The story revolves around the character of Mr. Roberts, who believes he has been robbed, only to realize he mistakenly took the watch of another man, Mr. Bemis. The plot begins with Mr. Roberts being accosted by an individual in a dark spot in the park, prompting him to pursue and tackle the supposed thief, leading to an ironic twist when he later discovers that the watch he recovered was not his own. The narrative humorously unfolds as Roberts navigates the complexities of his assault on Bemis, revealing themes of honor, societal expectations, and the absurdity of human behavior. His wife, Agnes, and their circle of friends react with a mix of concern, pride, and disbelief at the unfolding events. The novel culminates in a dinner party where the truth of the situation is slowly unraveled, providing both comedic relief and a moral reflection on the consequences of violence and misunderstanding among gentlefolk in society. (This is an automatically generated summary.)
Release date is 2002-05-01
Transcribed from the 1897 David Douglas edition by David Price
Keywords: American drama -- 19th century